Comparing the accuracy between shear wave elastography and strain elastography in the diagnosis of breast tumors: Systematic review and meta-analysis. Issue 18 (6th May 2022) - Wu, Huayu; Zhang, Shengnan; Wang, Cong; Yan, Yumei
Abstract: Background: Shear wave elastography and strain elastography are two new ultrasonic techniques developed rapidly in recent years. Changes in tissue elasticity occur after normal tissue changes. Elastography technique transforms the elastic information of tissue into optical information for display. Thus more intuitive display of tissue elasticity. Due to the differences in principles and related imaging parameters between the two elastic imaging methods, and the acquisition and interpretation of image data in strain elastic imaging method largely depends on the experience of inspectors, and due to the significant differences between the techniques of inspectors, As a result, conflicting results have been obtained in different scholars' studies on the accuracy comparison of the two elastography techniques in the diagnosis of breast tumors. This meta-analysis aims to compare the accuracy of the two elastography methods in the diagnosis of breast tumors, so as to provide more accurate diagnostic means for patients with breast tumors. The final results will show which elastography method is more accurate in the diagnosis of breast tumors, reduce unnecessary biopsies and provide a reference for clinical decision making. Methods: We will examine published and unpublished randomized controlled trials, observational studies and abstracts without publication type or language restrictions, and search relevant literatures in PubMed, Web of Science, Wanfang Database, CNQI and other databases until December 30, 2020. The authors will independently search relevant literature records, scan titles and abstracts, full text, collect data and assess the risk of bias. Data will be analyzed by using Meta Disc1.4 software and Stata14.0 software. Heterogeneity tests and combined sensitivity, specificity, positive and negative likelihood ratio, diagnostic odds ratio, and area under the summary receiver operating characteristic curve will be performed by using Meta Disc1.4 software. Stata14.0 software will be used for sensitivity analysis and publication bias test. Results: The results of this systematic review will demonstrate the accuracy of the two elastography methods in the diagnosis of breast tumors. Discussion: The results will provide useful evidence for the comparison of the diagnostic accuracy of shear wave elastography and strain elastography in breast tumors. Other: This study was not funded. Register name: PROSPERO. Registration number: CRD42021251110.